Simultaneous optimization of force and placement of friction dampers under seismic loading. Issue 4 (2nd April 2016) - Miguel, Letícia Fleck Fadel; Miguel, Leandro Fleck Fadel; Lopez, Rafael Holdorf
Abstract : It is known that the use of passive energy-dissipation devices, such as friction dampers, reduces considerably the dynamic response of a structure subjected to earthquake ground motions. Nevertheless, the parameters of each damper and the best placement of these devices remain difficult to determine. Some articles on optimum design of tuned mass dampers and viscous dampers have been published; however, there is a lack of studies on optimization of friction dampers. The main contribution of this article is to propose a methodology to simultaneously optimize the location of friction dampers and their friction forces in structures subjected to seismic loading, to achieve a desired level of reduction in the response. For this purpose, the recently developed backtracking search optimization algorithm (BSA) is employed, which can deal with optimization problems involving mixed discrete and continuous variables. For illustration purposes, two different structures are presented. The first is a six-storey shear building and the second is a transmission line tower. In both cases, the forces and positions of friction dampers are the design variables, while the objective functions are to minimize the interstorey drift for the first case and to minimize the maximum displacement at the top of the tower for the second example. The results show that the proposed method was able to reduce the interstorey drift of the shear building by more than 65% and the maximum displacement at the top of the tower by approximately 55%, with only three friction dampers. The proposed methodology is quite general and it could be recommended as an effective tool for optimum design of friction dampers for structural response control. Thus, this article shows that friction dampers can be designed in a safe and economic way.